A new chiral dimanganese(iii) complex: synthesis, crystal structure, spectroscopic, magnetic, and catalytic properties. Issue 89 (12th September 2016) - Dinca, Alina S.; Candu, Natalia; Shova, Sergiu; Lloret, Francesc; Julve, Miguel; Parvulescu, Vasile I.; Andruh, Marius
Abstract : The two enantiomeric dimanganese(iii ) complexes are efficient catalysts, with a total enantioselectivity, in the epoxidation of methyl trans -cinnamate. Abstract : Two enantiomeric complexes of formula [MnIII2(μ-OCH3 )2 ( R -valBINAM)2 ]·1.75DMF (1 ) and [MnIII2(μ-OCH3 )2 ( S -valBINAM)2 ]·2DMF (2 ) [valBINAM = 1, 1′-binaphthalene-2, 2′-bis(3-methoxysalicylideneiminate)] have been synthesized using as a ligand the chiral Schiff bases resulting from the condensation reactions between o -vanillin and the chiral 1, 1′-binaphthyl-2, 2′-diamine. The structures of1 and2 which have been solved by single crystal X-ray diffraction consist of neutral dimers, the manganese(iii ) ions being bridged by two methoxido anions, arising from the solvent, and by two valBINAM 2− ligands. Their circular dichroism spectra at room temperature emphasize the occurrence of the exciton coupling effect. The cryomagnetic measurements in the temperature range 2.0–300, for compound2, reveal the occurrence of antiferromagnetic interactions between the two Mn III ions ( J = −35.5 cm −1, the Hamiltonian being defined as H = − JS 1 S 2 ). The catalytic behaviour of these complexes was checked in the epoxidation of methyl trans -cinnamate with N -methylmorpholine- N -oxide as an oxidant. The influence of the solvent was also investigated. The reactions in a CH3 CN/H2 O (5 : 1 v/v) solvent mixture afforded total chemo- and enantioselectivity in the desired epoxides.